Picture editing - Ang, Tom (Focal Press, 2000)
This book has 4 steps: Step 1: The formulation of aim; Step 2: The sourcing of pictures, that is, obtaining them through original photography or from existing picture collections; Step 3: Assembling the selected pictures, with any associated information; Step 4: Readying the pictures for production.